The fintech transformation of banking: Governance dynamics and socio-economic outcomes in spatial contexts - Marta Gancarczyk; Piotr Łasak; Jacek Gancarczyk (Entrepreneurial Business and Economics Review (EBER), 2022)
Objective: The objective of the article is to identify and systemize the governance dynamics and related socio-economic consequences of the fintech transformation in banking, while acknowledging spatial contexts. Research Design & Methods: The research framework comprised Global Production Networks (GPN), Global Value Chain (GVC), and co-evolutionary approaches to guide a systematic literature review in the Scopus, Web of Science, and Taylor & Francis databases for 2016-2021. The final sample comprised 76 sources that became the basis for selective coding and the synthesis of the results. Findings: Fintech impacted banking governance by creating a dual and interrelated system of global financial networks and a 'mosaic' of territorial financial ecologies and ecosystems, where incumbent banks held an important but not exclusive position. The fintech-enhanced governance transformations had both positive socio-economic effects (improved efficiency, expanded range of services, and inclusion of unbanked or under-served customers) and negative effects (over-indebtedness, surveillance, and exclusion of some customers). Wider socio-economic consequences refered to sustainable development and changes in economic and social behaviour. Implications & Recommendations: A research framework and agenda for future studies related to the dynamics of fintech-driven governance in banking have been elaborated. The article derives the immediate and wider economic and social consequences of fintech-driven transformations. The results can also be applied in public policies oriented towards sustainable socio-economic development. Contribution & Value Added: The study provides theoretical and policy-relevant contributions. Firstly, it broadens the research on the transformation of banking governance in the spatial context. Secondly, it contributes theoretically by proposing a research framework of GVC and GPN governance augmented by a co-evolutionary perspective. Thirdly, the article informs policy that seeks financial inclusion for cohesive and sustainable development.
Keywords: F65; G21; L23; O14; 330; banking sector; fintech; governance; global production networks; global value chains